The effect of polyamine 70000 (BT70) on the zinc plating process in the non-cyanide alkaline plating bath - Nam, Truong Thi; Thang, Le Ba; Thanh Huong, Nguyen Thi; Khuong, Nguyen Van; Chien, Nguyen Van; Bao, Le Duc; Bich, Do Ngoc (Vietnam Journal of Chemistry, 2017)
The effect of polyamine having molecular weight 70,000u (BT70) in the non-cyanide alkaline plating bath on the morphological zinc electrodeposited coating was investigated. The obtained results from the reflectance of electrodeposited zinc coating by a suitable range of electro-current density and SEM images showed that BT70 had effect on the zinc plating in comparison with the zinc deposits from plating bath without BT70. The electrodeposited coating surface was rough and poor adhesion. However, adding BT70 into the plating bath led to the surface roughness of electrodeposited coating and grand size being reduced. Zinc electrodeposited coating from a plating bath containing BT70 at 0.5 g/L, respectively, experienced the highest reflectance, equal 46 % of the electrodeposited coating from the bath containing commercial additives. Hull method showed that the zinc deposited coating surface became smoother with the presence of polyamine in non-cyanide alkaline zinc plating solution. The zinc deposited coating had a semi-gloss scope at 10 A/dm2. If the BT70 content increased, the semi-gloss scop and the gloss of samples’ surfaces also grew up. Keywords. Polyamine, additive, non-cyanide alkaline zinc plating, zinc coating.